PAKEM BERBASIS SISTEM PERILAKU DALAM PENINGKATAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Reza Syehma Bahtiar (PGSD UNIKA SANTU PAULUS RUTENG, 2020)
This study aims to determine the success in increasing student motivation to learn PAKEM based on behavioural systems. This research is a type of qualitative research conducted at SDN Jajartunggal III Surabaya class I as many as 24 students. As for the research instrument, the observation sheet / observation sheet and the test sheet. In this study, the average results of completeness of the thinking skills test showed that of 24 students in grade 1 at SDN Jajartunggal III Surabaya, reaching 87.5%. These results have exceeded the percentage of assessment indicators 85% of all students. The results of the analysis of the discussion about the results of high-level essential thinking skills test (C3 - C6) for students during the learning process obtained that the first grade students of SDN Jajartunggal III Surabaya during the study reached a value of 87.5% of all students. The results of students' learning motivation obtained during the essential thinking skills test were 91.68%. This percentage has exceeded the percentage of research indicators 85% of all students who scored ≥75